ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENGUNGKAPAN SUKARELA PADA LAPORAN TAHUNAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia) - Adi Priguno; P. Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2013)
This study departs from the need for transparency of information in the annual reports of companies, considering the increasing number of companies that decide to go public. The increasingly level of annual report disclosure means the complete annual report will make it easier for users to know the actual condition of the company so that the company can be judged to be more transparent. The purpose of this study was to demonstrate empirically the factors that influence the level of annual report voluntary disclosure. The population is manufacture companies listed in Indonesia Stock Exchange period 2009-2011. Sampling technique using purposive sampling method. The dependent variable is the level of annual report voluntary disclosure, while the independent variable are leverage, liquidity, profitability, public shares and age of public companies. This study uses multiple linear regression method. Before using regression testing, previously use classical assumption test.The simultaneous (together) results showed that leverage, liquidity, profitability, public shares and age of public companies has a significant influence on the rate of annual report voluntary disclosure. But the partially result that only profitability and public shares has a significant influence on the rate of annual report voluntary disclosure.